Transitioning Out of the Coronavirus Lockdown: A Framework for Evaluating Zone-Based Social Distancing - Friedman, Eric; Friedman, John; Johnson, Simon; Landsberg, Adam (Frontiers in Public Health, 2020)
-In the face of elevated pandemic risk, canonical epidemiological models imply the need for extreme social distancing over a prolonged period. -Alternatively, people could be organized into zones, with more interactions inside their zone than across zones. -Zones can deliver significantly lower infection rates, with less social distancing, particularly if combined with simple quarantine rules and contact tracing. -This paper provides a framework for understanding and evaluating the implications of zones, quarantines, and other complementary policies.